Titanium dioxide nanotubes addition to self-adhesive resin cement: Effect on physical and biological properties - Ramos-Tonello, Carla M.; Lisboa-Filho, Paulo N. [UNESP]; Arruda, Larisa B. [UNESP]; Tokuhara, Cintia K.; Oliveira, Rodrigo C.; Furuse, Adilson Y.; Rubo, Jose H.; Borges, Ana Flavia S. (Elsevier B.V., 2017)
Objectives. This study has investigated the influence of Titanium dioxide nanotubes (TiO2-nt) addition to self-adhesive resin cement on the degree of conversion, water sorption, and water solubility, mechanical and biological properties. Methods. A commercially available auto-adhesive resin cement (RelyX U200(TM), 3M ESPE) was reinforced with varying amounts of nanotubes (0.3, 0.6, 0.9 wt%) and evaluated at different curing modes (self- and dual cure). The DC in different times (3, 6, 9, 12 and 15 min), water sorption (Ws) and solubility (Sl), 3-point flexural strength (sf), elastic modulus (E), Knoop microhardness (H) and viability of NIH/3T3 fibroblasts were performed to characterize the resin cement. Results. Reinforced self-adhesive resin cement, regardless of concentration, increased the DC for the self- and dual-curing modes at all times studied. The concentration of the TiO2-nt and the curing mode did not influence the Ws and Sl. Regarding sf, concentrations of both 0.3 and 0.9 wt% for self-curing mode resulted in data similar to that of dual-curing unreinforced cement. The E increased with the addition of 0.9 wt% for self-cure mode and H increased with 0.6 and 0.9 wt% for both curing modes. Cytotoxicity assays revealed that reinforced cements were biocompatible. Significance. TiO2-nt reinforced self-adhesive resin cement are promising materials for use in indirect dental restorations. Taken together, self-adhesive resin cement reinforced with TiO2-nt exhibited physicochemical and mechanical properties superior to those of unreinforced cements, without compromising their cellular viability. (C) 2017 The Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Dental cements; Polymerization; Nanotechnology; Nanotubes; Titanium; Physical and chemical properties; Mechanical phenomena